Granisetron transdermal system and dexamethasone for the prevention of nausea and vomiting in multiple myeloma patients receiving chemo-mobilization: An observational real-world study of effectiveness and safety. (December 2020) - Martino, Massimo; Naso, Virginia; Porto, Gaetana; Paviglianiti, Annalisa; Ferreri, Anna; Loteta, Barbara; Moscato, Tiziana; Console, Giuseppe; Gentile, Massimo; Rossi, Marco; Provenzano, Pasquale Fabio; Gori, Mercedes; et al.
Abstract: PURPOSE: Cyclophosphamide (CY) in a dose of 2–4 g/m 2 is widely used for hemopoietic progenitor stem cells mobilization. CY administration is associated with several adverse effects, including chemotherapy-induced nausea and vomiting (CINV). This study aimed to evaluate the efficacy and tolerability of granisetron transdermal system (GTDS) plus dexamethasone in the management of CINV in MM patients undergoing chemo-mobilization with CY. METHODS: In this single-center, prospective, observational, real world study, GTDS plus dexamethasone was administered to MM patients receiving chemo-mobilization based on CY 2 g/m2 plus G-CSF in an outpatient setting. The rate of complete response was evaluated as the main outcome. Other outcomes were rate of complete control of CINV, incidence of nausea/vomiting of any grade and safety. RESULTS: A total of 88 patients were enrolled. A complete response was achieved in 45.5 % of patients; among them, 39.77 % attained complete control of CINV. Nausea and vomiting never occurred in 34.1 % and 45.5 % of patients, respectively. No episodes of grade 3–4 nausea and/or vomiting were documented. GTDS was safe and well tolerated. CONCLUSION: In real world, GTDS provided an innovative, effective, and well-tolerated control of CINV in MM patients after chemo-mobilization with CY. The study found out effectiveness of a non-invasive delivery system of antiemetic.